Propuesta de la estructura organizacional y administrativa para la empresa Agrofertil Granada S.A.S. Zomac (2022)
This degree project compiles the diagnostic process of the organizational structure of the company AgroFertil Granada S.A.S. Zomac, located in the department of Meta and recognized for its history as a distributor and marketer of agro-industrial supplies for crops in the region. Initially, the analysis was developed through a SWOT matrix, which allowed reviewing the shortcomings within the organizational structure that, in addition, affected the normal development of the processes and prevented it from approaching the fulfillment of its mission and vision; likewise, the opportunities and advantages of the organization to improve the provision of its service through the formalization of its organizational structure. Then, through the methodology proposed by Baca Urbina, was proposed a process organization chart model, which considers the strategic objectives of the company and the need for human resources within the processes that are carried out. Finally, some recommendations were established for the establishment of the organizational chart within the organization and its formalization. From all of the above and fulfilling the main objective of this project, it was possible to generate the organizational structure proposal for the company according to its needs and characteristics, in addition to the approach of the value proposal, so that the strategies are directed towards the fulfillment of the mission and vision.